SANGGAHAN ATAS TEORI INGKAR AS-SUNNAH JOSEPH SCHACHT - Munandar Munandar (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“Joseph Schacht is a legal historian who gives many benefits of science, either about the development of the history of Islamic Law or about the sunnah of the Prophet. His works dominated Fikih (Islamic Law), the main work of The Origins Of Muhammadan Jurisprudence and An Introduction to Islamic Law. His project of criticism of Islamic law has cast doubt on the crucial role of contributing hadith to the development of Islamic Law. In fact, he specifically argues that the hadith in essence contains only those that are ethical and few are legal. He also denied the existence of an important role of hadith against the development of an important Islamic Law.”